Anticipatory Thinking in Multi-Agent Contexts - Hübner, Jomi F.; Burattini, Samuele; Ricci, Alessandro; Mayer, Simon (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2025: Anais do XIX Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2025)
Anticipatory thinking allows agents to foresee and avoid future problems by exploiting their plan libraries. This paper extends previous work on anticipatory thinking for single agents to the domain of Multi-Agent Systems (MAS), where the environment’s evolution depends on the combined actions of multiple autonomous agents. We detail how an agent can simulate potential futures in a multi-agent context, considering the preferred policies of all participants, to anticipate and react to undesirable outcomes. Our proposed strategies enable an agent to either abandon a goal if a problem is inevitable or dynamically select an alternative plan to avoid anticipated problems. Experiments in a Bridge Scenario, a classic Multi-Agent Pathfinding problem, yield a critical insight: anticipatory thinking, in isolation, only resolves the conflict when exactly one agent exercises this foresight. When multiple agents independently reason about the future, the problem re-emerges, indicating a fundamental limitation of purely individualistic anticipation and stressing the importance of future research into integrated anticipatory thinking and coordination.